2017
DOI: 10.1021/acs.jpcb.7b02714
|View full text |Cite
|
Sign up to set email alerts
|

Protonation States of Homocitrate and Nearby Residues in Nitrogenase Studied by Computational Methods and Quantum Refinement

Abstract: Nitrogenase is the only enzyme that can break the triple bond in N to form two molecules of ammonia. The enzyme has been thoroughly studied with both experimental and computational methods, but there is still no consensus regarding the atomic details of the reaction mechanism. In the most common form, the active site is a MoFeSC(homocitrate) cluster. The homocitrate ligand contains one alcohol and three carboxylate groups. In water solution, the triply deprotonated form dominates, but because the alcohol (and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
167
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 71 publications
(181 citation statements)
references
References 108 publications
14
167
0
Order By: Relevance
“…Future studies will reveal the importance of this proton in conjunction with other protonation pathways near FeMoco. Finally, we note that Ryde et al 27 have recently come to the same conclusions regarding the protonation state of homocitrate using a combination of QM/MM calculations, pK a calculations via thermochemical cycles and quantum crystal refinement. D. QM region size dependence: structures, vertical redox reactions and deprotonations Large QM regions have been used in the geometric analysis of FeMoco in this study.…”
Section: Protonation State Of Homocitratesupporting
confidence: 63%
See 1 more Smart Citation
“…Future studies will reveal the importance of this proton in conjunction with other protonation pathways near FeMoco. Finally, we note that Ryde et al 27 have recently come to the same conclusions regarding the protonation state of homocitrate using a combination of QM/MM calculations, pK a calculations via thermochemical cycles and quantum crystal refinement. D. QM region size dependence: structures, vertical redox reactions and deprotonations Large QM regions have been used in the geometric analysis of FeMoco in this study.…”
Section: Protonation State Of Homocitratesupporting
confidence: 63%
“…Cao et al 25 were the first to perform a quantum mechanics/molecular mechanics (QM/MM) study of the MoFe protein, during the time when the interstitial atom of FeMoco was unknown and concluded that the interstitial atom was an oxygen. Recently Adamo 26 et al used QM/QM' calculations to propose new mechanisms and Ryde et al studied protonation states by QM/MM 27 . In previous articles by one of us (RB) we utilized large 225-atom cluster models in our studies of the spectroscopic properties of the FeMo cofactor 28,29,30,31,32 .…”
Section: Introductionmentioning
confidence: 99%
“…All calculations were based on the 1.0‐Å crystal structure of nitrogenase from Azotobacter vinelandii (PDB code 3U7Q) . The setup of the protein is identical to that of our previous study of the protein . The entire heterotetramer was included in the calculations, because the various subunits are entangled without any natural way to separate them.…”
Section: Methodsmentioning
confidence: 99%
“…This approach has later been extended to other software, including also QM/MM and ab initio methods. [51,52,137,138,[141][142][143][145][146][147][148][149] Typical applications regard the nature,p rotonation and oxidation state of the active site, comparing different structural alternatives, as shown in Figure 4. Eur.J.…”
Section: Wavefunction-based Refinementmentioning
confidence: 99%
“…[149] The 2mF o -DF c maps are contoured at 1.0 s and the mF o -DF c maps are contouredat+ 3.0 s (green)and À3.0 s (red). Electron-density maps of two possible protonation states of the homocitrate ligand in nitrogenase.…”
Section: Wavefunction-based Refinementmentioning
confidence: 99%